Food Worry in the Deaf and Hard-of-Hearing Population During the COVID-19 Pandemic. (March 2021) - Engelman, Alina; Paludneviciene, Raylene; Wagner, Kathryn; Jacobs, Katja; Kushalnagar, Poorna
Objective: The coronavirus disease 2019 (COVID) pandemic has highlighted preexisting health disparities, including food insecurity, in the deaf and hard-of-hearing (DHH) population. We examined factors associated with food worry during the COVID-19 pandemic. Methods: We collected survey data on worry about food shortages, worry about contracting COVID-19, and concerns about DHH people staying home and being lonely from April 17 through May 1, 2020, via a bilingual American Sign Language/English online survey platform. The sample consisted of 537 DHH adults living in the United States. We examined the relationship between demographic characteristics and food worry. We used logistic regression and model fitting to predict the likelihood of experiencing food worry. Results: The mean (SD) age of survey respondents was 47 (16), and 25% of the sample identified as people of color. Forty-two percent of survey respondents had a high level of food worry. Increased worry about contracting COVID-19 and concerns about DHH people staying home and being lonely among DHH younger adults or those without a college degree predicted food worry. Gender and race/ethnicity did not contribute to the model for food worry. Conclusions: Food worry was explained by multiple, intersecting factors, including demographic variables, worry about contracting COVID-19, and concerns about loneliness. Interventions or programs implemented by DHH-serving organizations as well as government programs, social service providers, and food banks should be fully accessible to subgroups of DHH young adults without a college degree who are at risk for food insecurity.